Determination of diquat and paraquat by high performance liquid chromatography in areas of environmental monitoring - I.M. Fitsev; A.Yu. Likhacheva; A.M. Sayfutdinov; A.Z. Mukharlyamova; S.L. Mokhtarova; Z.R. Nasybullina (Учёные записки Казанского университета: Серия Естественные науки)
The concentrations of diquat and paraquat, two members of the class of quaternary ammonium compounds (QAC), were measured using high performance liquid chromatography (HPLC) with UV detection and sample preparation with solid phase extraction. The results obtained during the HPLC determination of diquat and paraquat were confirmed by the method of HPLC – quadrupole time-of-flight mass spectrometry (HPLC-MS) with electrospray ionization. Diquat (0.17 ? 0.02 mg/kg on average, i.e., below its maximum permissible level) was found in the soil samples used to cultivate sunflower, wheat, and potato. In the surface waters of the natural water bodies adjacent to the agricultural lands treated with diquat and paraquat, no QAC compounds were found.